2020
DOI: 10.1186/s13017-020-00329-w
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes of blunt renal trauma management: a nationwide cohort study in Japan

Abstract: Background: There is a paucity of information for predicting patient outcomes other than the American Association for the Surgery of Trauma (AAST) renal injury scale. The aim of this study was to evaluate the association between the patient characteristics and outcomes of patients with blunt renal trauma using a nationwide database in Japan. Methods: We performed a retrospective analysis of the Japan Trauma Data Bank (JTDB) from 2004 to 2018. We identified patients with blunt renal trauma by AIS codes converte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…The median age of the patients with renal traumatic injury in our study was similar to that of a nationwide study in Japan [ 15 ] but was higher than that of a study in the United States [ 16 ]. The median ISS and mortality in our study were lower than those of previous studies in Japan and the United States.…”
Section: Discussionsupporting
confidence: 81%
“…The median age of the patients with renal traumatic injury in our study was similar to that of a nationwide study in Japan [ 15 ] but was higher than that of a study in the United States [ 16 ]. The median ISS and mortality in our study were lower than those of previous studies in Japan and the United States.…”
Section: Discussionsupporting
confidence: 81%
“…The median age of the patients with renal traumatic injury in our study was similar to that of a nationwide study in Japan 15 but was higher than that of a study in the United States. 16 The median ISS and mortality in our study were lower than those of previous studies in Japan and the United States.…”
Section: Discussionsupporting
confidence: 80%
“…The kidney is only held in position by the renal pelvis and vascular pedicle, therefore, it is particularly vulnerable to decelerating injuries, such as falls, and motor vehicle collisions [3]. Studies have shown that falls and car accidents are the most common causes of renal injury [2,5,18,19]. In a retrospective study over 15 years, using data from the Japan Trauma Data Bank, patients with blunt renal trauma were identified (n = 3,550) and falls accounted for 34% of injuries, and car accidents accounted for 15.7% [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that falls and car accidents are the most common causes of renal injury [2,5,18,19]. In a retrospective study over 15 years, using data from the Japan Trauma Data Bank, patients with blunt renal trauma were identified (n = 3,550) and falls accounted for 34% of injuries, and car accidents accounted for 15.7% [18]. Another retrospective study over 8 years using the Taiwan National Trauma Bank (n = 10,096) reported that the most common mechanisms of renal injury were motor vehicle accidents (49.4%) and falls (27.4%) [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation